Perceptions of Citizen Affiliated with Community Based Institutions on Social Norms and Practices Related Adolescent Sexual and Reproductive Health in Baitadi District of Nepal - Panthi, Giri Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2017)
The study attempted to explore and analyze perceptions of citizens affiliated with Community Based Institutions on social norms and practices related to adolescent sexual and reproductive health in Baitadi district of Nepal. The objective of this study was to assess social acceptance level of citizen to challenge prevailing social norms and their readiness to abandon unhealthy traditional practices related to sexual and reproductive health as a social accountability. Descriptive and analytical research design was used to take the citizens perspectives. A total of 337 respondents affiliated with the five different types of Community Based Institutions (CBIs) were interviewed using structured questionnaire for data collection and data analysis was done by using SPSS version 16.0. The findings of the study revealed that majority of citizens were sticky on traditional social norms and practices. Majority of citizens were not agree to allow adolescent girls to go to school during mensuration, to allow to stay inside home during mensuration and talking about sex and sexuality between parents and adolescents. Therefore, there is a need of social norms change and step up for positive social deviant by citizen leaders to promote enabling social environment for adolescent sexual and reproductive health. Dhaulagiri Journal of Sociology and Anthropology Vol.11, 2017; 151-163